Om dannelse. Tale af N. F. S Grundtvig i »Danske Samfund« 4. maj 1841 - Johansen, Steen (Grundtvig-Studier, 1955)
“On Cul tureA Lecture by N. F. S. Grundtvig to the “Danish Society” on May 4th, 1841. Contributed, with notes and a postscript, by Steen Johansen. In 1839 Grundtvig assisted in founding a little association in Copenhagen, called the “Danish Society”, our first truly Danish Lecture Society. During the first three or four years Grundtvig was as a matter of course the intellectual leader of the Society, and his aim was to awaken the nation to be Danish, to be true to its own national character, and to be inspired with love of country. Virtually all Grundtvig’s lectures to the Society have been preserved in manuscript, but most of them have hitherto been unknown to, and unused by, those engaged in Grundtvigian research. One of the lectures, to which our contributor has given the title “On Culture”, is printed here, provided with explanatory notes and a postscript about Grundtvig’s activities in the Society. In this lecture Grundtvig distinguishes between false and true culture, i. e., between a culture which is the result of a purely superficial acquisition of knowledge about the world around, hasty reading of newspapers, etc., and a culture which is synonymous with enligthened humanity, understanding of one’s fellow-men, a culture which does not depend on circumstances or position, but can be found even in the poorest peasant. In order to possess true culture one must also, according to Grundtvig, be able to express oneself correctly and fluently about all that we experience, think and feel, and must be able to enter into the situations of other people and into everything that has to do with our fatherland. True culture thus prepares the way for the national spirit and is indispensable in a national legislature.